1994
DOI: 10.3758/bf03199920
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative transfer of conditioned aversive stimuli to a conditioned appetitive excitor as a function of aversive US intensity

Abstract: Rats were given Pavlovian aversive (Av) conditioning in which a weak (O.5-sec, O.7-rnA) or a strong (O.5-sec, lA-rnA) footshock unconditioned stimulus (US) was presented alone or in a positive, zero, or negative correlation with a flashing-light conditioned stimulus (AvCS+, AvCSo, or AvCS-, respectively). Thereafter, the subjects received Pavlovian appetitive (Ap) conditioning in which the flashing-light CS was positively correlated in a forward order with the delivery of a food US. As anticipated, for subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Evidence drawing on different methods to assess the motivational nature of prevention relief adds to this ambiguity. While some studies bolster the notion that safety stimuli boost appetitive motivation ( Bromage and Scavio, 1978 ), other studies again suggest that this is highly moderated ( DeVito and Fowler, 1994 ). Additionally, there is evidence that safety stimuli induce approach motivation in the sense that animals develop a preference for the place of their occurrence ( Rogan et al, 2005 ) and are faster to run toward prevention relief signals ( Haraway et al, 1984 ).…”
Section: Evidencementioning
confidence: 98%
“…Evidence drawing on different methods to assess the motivational nature of prevention relief adds to this ambiguity. While some studies bolster the notion that safety stimuli boost appetitive motivation ( Bromage and Scavio, 1978 ), other studies again suggest that this is highly moderated ( DeVito and Fowler, 1994 ). Additionally, there is evidence that safety stimuli induce approach motivation in the sense that animals develop a preference for the place of their occurrence ( Rogan et al, 2005 ) and are faster to run toward prevention relief signals ( Haraway et al, 1984 ).…”
Section: Evidencementioning
confidence: 98%
“…The grid floor delivered scrambled footshock of 1 .O mA from a BRS/LVE Generator (Model SBS-004). The level and durations of shock employed in this study are within the range reported for rats of these ages in various tasks (e.g., DeVito & Fowler, 1994;Miller & Spear, 1989;Myslivecek & Hassmannova, 1990). Tonal stimuli were produced by a T1 SN76496 programmable generator through two 40-cm Quam speakers, one mounted on the ceiling of each compartment in the center area with perforations drilled into the plastic.…”
Section: Apparatusmentioning
confidence: 66%
“…This form of positive reinforcement was explained by Dickinson and Dearing in terms of an opponent process between appetitive and aversive motivational systems under which a conditioned aversive inhibitor activates the appetitive motivational system and thereby functions like a conditioned appetitive excitor (Dickinson & Dearing, 1979). A variety of evidence confirms this functional equivalence -for example, DeVito and Fowler reported that training a flashing light as aversive inhibitor facilitates subsequent appetitive conditioning to this stimulus (DeVito & Fowler, 1994), whereas appetitive conditioning is blocked when conducted in the presence of an aversive inhibitor (Dickinson & Dearing, 1979;Laurent et al, 2018).…”
mentioning
confidence: 90%